Management of Osteogenesis Imperfecta - Ralston, Stuart H.; Gaston, Mark S. (Frontiers in Endocrinology, 2020)
Osteogenesis imperfecta (OI) refers to a group of rare inherited skeletal disorders characterised by a greatly increased risk of fragility fractures (1). Mutations in several genes can cause OI but the condition is most commonly caused by mutations of COLIA1 or COL1A2 resulting in the production of collagen which is abnormal or present in reduced amounts. Fractures in OI are particularly common during childhood but the elevated fracture risk continues throughout life. Bone mineral density (BMD) can be reduced in OI but the magnitude of increase in fracture risk is far greater that can be accounted for by low BMD highlighting that a key mechanism of bone fragility is reduced bone quality due to defects of bone matrix and mineralisation. A multidisciplinary approach is needed to optimise management of OI, with input from physicians, orthopaedic surgeons, physiotherapists, occupational therapies and other allied health professionals. Orthopaedic surgery plays a key role both in the fixation of fractures and in the correction of limb deformities. Bisphosphonates have been widely used in the treatment of children and adults with OI. Although there is good evidence that they increase BMD, it is uncertain to what extent they reduce fracture risk. Clinical trials of bone anabolic drugs such as teriparatide and inhibitors of sclerostin have also been studied; although they increase BMD, studies of these agents have not been powered to look at fracture endpoints. Various other treatment modalities including denosumab, and cell therapy have been explored but haven’t gained acceptance in routine clinical practice. There have been huge advances in understanding the pathogenesis of OI but these have not been accompanied by advances in treatment. This signals need for well-designed clinical trials with fracture endpoints in OI, both with existing agents and with the newer therapeutic agents that are now starting to emerge